The Influence of Brand Engagement and Customer Experience Mediated by Brand Trust on Customer Loyalty - Tesalonika, Putri; Marvianta, YB Andre (Universitas muhammadiyah malang, 2026)
Increasingly intense business competition requires companies to build strong relationships with customers through brand engagement and customer experience. Brand trust plays a crucial role in shaping customer loyalty. This study aims to analyze the influence of brand engagement and customer experience on customer loyalty, with brand trust as a mediating variable. The research employs a quantitative approach using a survey method. Data were collected through questionnaires and analyzed using statistical analysis techniques to examine the relationships among the research variables. The results indicate that brand engagement and customer experience have a positive effect on brand trust. Furthermore, brand trust is proven to have a significant effect on customer loyalty, thereby acting as a mediating variable in this relationship. Brand engagement and customer experience are able to enhance customer loyalty through the development of trust in the brand. Companies are therefore advised to improve the quality of customer interactions and create positive experiences to strengthen brand trust and customer loyalty.